Christian summer camps for Indigenous youth in Canada: a settler colonial analysis. Issue 2 (3rd April 2023) - Rumford-Rodgers, Hope; Giles, Audrey R.; Scobie, Willow
ABSTRACT: The Truth and Reconciliation Commission of Canada's Final Report and Calls to Action highlighted the need for the truth about Indian residential schools to be known and the responsibility of churches and religious groups to take action to enact reconciliation with Indigenous peoples. Summer camps for Indigenous youth run by Christian organizations in Canada are sites that have not yet been given scholarly attention. Within this context, 'What is happening in these spaces' is a simple question, but one behind which is the heavy weight of residential school history and the TRC's Calls to Action. In this paper, we share the results of our research, which was informed by a settler colonial studies lens, and internet-mediated document analysis of camp websites, as well as questionnaires and semi-structured interviews completed with those who operate and work at these camps. Our research addresses an important, but neglected, area of study and makes a timely and applied contribution to leisure studies.